SKIRINING FITOKIMIA DAN UJI ANTIAGREGASI PLATELET EKSTRAK DAUN LAMPENI (Ardisia humilis) ASAL PULAU PEUCANG TAMAN NASIONAL UJUNG KULON - Fransiska Tinambunan (Scripta Biologica, 2022)
Lampeni (Ardisia humilis) is a plant that can be found in Peucang Island, Ujung Kulon National Park. Lampeni are used as medicinal plants because they can produce secondary metabolites. The purpose of this study was to determine the phytochemical content and antiaggregation platelets potential of lampeni leaf. This research was conducted in September-October 2018 on Peucang Island and UNJ Biochemistry Laboratory. The phytochemical content of the lampeni leaf was in the form of alkaloids, flavonoids, terpenoids, saponins and tannins and platelet aggregation test using the Pimentel method. Lampeni leaf extract was made using simplicia and solvent which is 1:10 (w/v) with 70% ethanol solvent.  The results of the phytochemicals content test on the lampeni leaf contain alkaloids, flavonoids, terpenoids and saponins but do not contain tannins. The results of platelet aggregation test showed there was no formation of violet gel which indicated that platelet aggregation did not occur so that the lampeni leaf had the ability as an anti-aggregate platelet.